Aged mice show an increased mortality after anesthesia with a standard dose of ketamine/xylazine - Sandra Schuetze; Anja Manig; Sandra Ribes; Roland Nau (Laboratory Animal Research, 2019)
Abstract Geriatric animal models are crucial for a better understanding and an improved therapy of age-related diseases. We observed a high mortality of aged mice after anesthesia with a standard dose of ketamine/xylazine, an anesthetic regimen frequently used in laboratory veterinary medicine. C57BL/6-N mice at the age of 2.14 ± 0.23 months (young mice) and 26.31 ± 2.15 months (aged mice) were anesthetized by intraperitoneal injection of 2 mg ketamine and 0.2 mg xylazine. 4 of 26 aged mice (15.4%) but none of 26 young mice died within 15 min after injection of the anesthetics. The weight of aged mice was significantly higher than that of young mice (32.8 ± 5.4 g versus 23.2 ± 3.4 g, p < 0.0001). Thus, aged mice received lower doses of anesthetics in relation to their body weight which are within the lower range of doses recommended in the literature or even beneath. There were no differences between deceased and surviving aged mice concerning their sex, weight and their motor performance prior to anesthesia. Our data clearly show an age-related increase of mortality upon anesthesia with low standard doses of ketamine/xylazine. Assessment of weight and motor performance did not help to predict vulnerability of aged mice to the anesthetics. Caution is necessary when this common anesthetic regimen is applied in aged mice: lower doses or the use of alternative anesthetics should be considered to avoid unexpected mortality. The present data from our geriatric mouse model strongly corroborate an age-adjusted reduction of anesthetic doses to reduce anesthesia-related mortality in aged individuals.